PENERAPAN PEMBELAJARAN INKUIRI TERBIMBING (GUIDED INQUIRY) UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN KOLOID DI KELAS XI IPA SMA NEGERI 14 PEKANBARU - Putri Qori Utami; Maria Erna; Rasmiwetti ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The research aims to improve student learning achievement on the topic of colloid in XI science class of SMAN 14 Pekanbaru by implementation of guided inquiry learning. The research was a form of experimental research with the design Randomized Control Group Pretest-Posttest. The sample consists of two classes, class XI science 3 as an experimental class and class XI science 2 as the control class is determined randomly after normality test and homogeneity test. Experimental class was implied of guided inquiry learning while the control class didn’t imply of guided inquiry learning. Data analysis technique used is the t-test. Based on the results of data processing obtained tcount > ttable is 5,67 > 1,67 means that the implementation of guided inquiry learning can improve student learning achievement on the topic of colloid in XI science class of SMAN 14 Pekanbaru. The effect implementation of guided inquiry learning to students’ learning achievement improve is about 36,07%.Keywords: Guided Inquiry Learning, Learning Achievement, Colloid